Primary cardiac myxofibrosarcoma of the left atrium and pericardium: a case report - Ryota Azuma; Kazuyoshi Sato; Hiroki Sunadoi; Yasushi Ishii; Utano Tomaru; Masatoshi Motohashi (Journal of Cardiothoracic Surgery, 2023)
Abstract Background Primary cardiac myxofibrosarcoma is rare and commonly occurs in the left atrium. Myxofibrosarcoma is aggressive and has a high mortality rate due to its high rate of recurrence. Complete surgical resection is considered important; however, effective treatment options have not been established. Case presentation We report the case of a 75-year-old woman who developed a myxofibrosarcoma spreading to the left atrium and pericardium. We performed surgical resection of the tumor to prevent sudden death due to mitral valve obstruction or cerebral infarction due to embolism of the scattered mass. However, we were unable to complete the resection of the tumors. The patient developed brain metastasis 2 months after surgery and eventually died due to brain hemorrhage 3 months after surgery. Conclusions In this report, we described a rare case of primary cardiac myxofibrosarcoma located not only in the left atrium but also in the pericardium. Considering preoperative laboratory findings, surgical and adjuvant therapy, and the patient’s wishes are important for the best therapeutic course for an individual.